A Review on Sustainable Development of Geological Exploration Technology and Risk Management - Liang, Rui; Tang, Panke; Xiong, Guoxiang; Liu, Ziyang; Yu, Dandan (Recent Patents on Engineering, 2021)
Background: Environmental protection is increasingly being emphasized upon, and higher requirements are put forward for the development of the geological prospecting industry. Researchers have been trying their best to explore the mineral resources in the deep part of the earth and the areas with poor working conditions, and avoid the damage of mining development to the environment, so as to achieve the goal of green prospecting and sustainable geological exploration. Methods: This greatly increases the uncertainty of ore prospecting and requires the traditional technical means to be improved. With the great progress of computer hardware and software, the application of geophysical exploration, geochemical exploration, remote sensing, and other methods that have little damage to the environment, have been improved. A reasonable technology mix can be used more efficiently and explored in a cost-effective way. Conclusion: According to the requirements of green and sustainable exploration, geophysical exploration, geochemical exploration and remote sensing can acquire surface data of a certain area more quickly with less economic cost and lower environmental impact, so as to provide decision for the next step of prospecting and avoid the risk to a greater extent. The prospecting information obtained by the three methods cannot directly control mine. The specific method selection and combination need to consider the actual demand, in order to complete the geological exploration work better and with rational use of funds.
Keywords: remote sensing technology